Multicultural and multilingual educator professionalism - Ulla Lundqvist; Signe Hvid Thingstrup; Annika Åkerblom (Nordic Journal of Comparative and International Education)
This article investigates how multicultural and multilingual educator professionalism unfolds as a dynamic phenomenon among educators in Danish and Swedish preschools and primary schools. Reflexive dialogues were produced with educators in three different action research studies. These dialogues were analysed by employing conceptual approaches of educator professionalism, equity pedagogy, and multicultural and multilingual education. The analyses show how the educators: (i) critically examine their constructions of pupils/children, (ii) develop increasingly broad views on how knowledge and learning can be productively produced in classroom interaction, and (iii) show awareness about societal language ideologies. The educators’ nuanced reflections on their own pedagogical practices displayed contradictions and ambivalences. We argue that the educators’ reflections point to possible renewals of pedagogical practices that place multiculturalism and multilingualism at the centre of educator professionalism.